Dexamethasone retrodialysis attenuates microglial response to implanted probes in vivo - Kozai, Takashi D.Y. (Biomaterials, 2016)
Intracortical neural probes enable researchers to measure electrical and chemical signals in the brain. However, penetration injury from probe insertion into living brain tissue leads to an inflammatory tissue response. In turn, microglia are activated, which leads to encapsulation of the probe and release of pro-inflammatory cytokines. This inflammatory tissue response alters the electrical and chemical microenvironment surrounding the implanted probe, which may in turn interfere with signal acquisition. Dexamethasone (Dex), a potent anti-inflammatory steroid, can be used to prevent and diminish tissue disruptions caused by probe implantation. Herein, we report retrodialysis administration of dexamethasone while using in vivo two-photon microscopy to observe real-time microglial reaction to the implanted probe. Microdialysis probes under artificial cerebrospinal fluid (aCSF) perfusion with or without Dex were implanted into the cortex of transgenic mice that express GFP in microglia under the CX3CR1 promoter and imaged for 6 hours. Acute morphological changes in microglia were evident around the microdialysis probe. The radius of microglia activation was 177.1 μm with aCSF control compared to 93.0 μm with Dex perfusion. T-stage morphology and microglia directionality indices were also used to quantify the microglial response to implanted probes as a function of distance. Dexamethasone had a profound effect on the microglia morphology and reduced the acute activation of these cells.